On Some Relationships of Certain K−Uniformly Analytic Functions Associated with Mittag-Leffler Function. (28th May 2021) - Attiya, Adel A.; Ali, Ekram E.; Hassan, Taher S.; Albalahi, Abeer M.
Abstract : In this paper, we introduce and investigate several inclusion relationships of new k - uniformly classes of analytic functions defined by the Mittag-Leffler function. Also, integral-preserving properties of these classes associated with the certain integral operator are also obtained.